2021
DOI: 10.1002/jdn.10153
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sodium channels on neurological/neuronal disorders: A systematic review

Abstract: Neurological and neuronal disorders are associated with structural, biochemical, or electrical abnormalities in the nervous system. Many neurological diseases have not yet been discovered. Interventions used for the treatment of these disorders include avoidance measures, lifestyle changes, physiotherapy, neurorehabilitation, pain management, medication, and surgery. In the sodium channelopathies, alterations in the structure, expression, and function of voltage-gated sodium channels (VGSCs) are considered as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 200 publications
(215 reference statements)
0
8
0
Order By: Relevance
“…Additionally, CoQ10 regulates the activity of NO synthases [4]. Studies have demonstrated that coenzyme Q10 exhibits both inhibitory effects on iNOS and eNOS, as evidenced by Erol B in 2009 [6], 2 and stimulatory effects, as confirmed in an experimental rat model of seizures with the activation of constitutive NOS [7].…”
Section: Biological Functions Of Coenzyme Q10mentioning
confidence: 93%
See 3 more Smart Citations
“…Additionally, CoQ10 regulates the activity of NO synthases [4]. Studies have demonstrated that coenzyme Q10 exhibits both inhibitory effects on iNOS and eNOS, as evidenced by Erol B in 2009 [6], 2 and stimulatory effects, as confirmed in an experimental rat model of seizures with the activation of constitutive NOS [7].…”
Section: Biological Functions Of Coenzyme Q10mentioning
confidence: 93%
“…It also regulates the activity of NFkB nuclear transcription factors, impacting the activity of inflammosomes and reducing the production of pro-inflammatory cytokines. CoQ10 is involved in apoptosis and mitophagy processes, in particular in regulation of the activity of apoptosis proteins [4,5].…”
Section: Biological Functions Of Coenzyme Q10mentioning
confidence: 99%
See 2 more Smart Citations
“…Non-selective VGSC inhibitors have been studied for decades, and their utility has been proven in clinical settings. 42–44,50 Their common characteristics are weak VGSC inhibitory activity with modest subtype selectivity. Their inhibitory activity is usually in the micromolar range.…”
Section: Conventional Vgsc Inhibitorsmentioning
confidence: 99%